Consensus statement on the use of rituximab in patients with rheumatoid arthritis. Issue 2 (26th October 2006) - Smolen, J S; Keystone, E C; Emery, P; Breedveld, F C; Betteridge, N; Burmester, G R; Dougados, M; Ferraccioli, G; Jaeger, U; Klareskog, L; Kvien, T K; Martin-Mola, E; et al.
Abstract : A large number of experts experienced in the treatment of rheumatoid arthritis were involved in formulating a consensus statement on the use of B cell-targeted treatment with rituximab in patients with rheumatoid arthritis. The statement was supported by data from randomised controlled clinical trials and the substantial literature on oncology. The statement underwent three rounds of discussions until its ultimate formulation. It should guide clinicians in the use of this newly approved biological agent in treating patients with rheumatoid arthritis.